2011
DOI: 10.1111/j.1748-1716.2011.02301.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive in vivo imaging of pancreatic β‐cell function and survival – a perspective

Abstract: A major problem in medical research is to translate in vitro observations into the living organism. In this perspective, we discuss ongoing efforts to non-invasively image pancreatic islets/β-cells by techniques, such as magnetic resonance imaging and positron emission tomography, and present an experimental platform, which allows in vivo imaging of pancreatic β-cell mass and function longitudinally and at the single-cell level. Following transplantation of pancreatic islets into the anterior chamber of the ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…In recent years, opportunities to assess β-cell mass using imaging have evolved with the development of β-cell-targeting peptide dyes 37 and antibody–dye conjugates 38 , but these are generally reserved to excised tissue samples requiring invasive procedures. Alternatively, nanoprobes are being developed with β-cell specificity and high contrast 39 , which may enable clinicians and researchers to non-invasively quantify in vivo endogenous β-cell mass 40 , survival of exogenous transplanted islets 41 and the performance of islet cells in cell replacement therapy 4246 . Various non-invasive imaging techniques are being investigated for the visualization of β-cell mass, including computed tomography (CT), positron emission tomography (PET) and magnetic resonance imaging (MRI) 47 .…”
Section: Diagnosis and Disease Monitoringmentioning
confidence: 99%
“…In recent years, opportunities to assess β-cell mass using imaging have evolved with the development of β-cell-targeting peptide dyes 37 and antibody–dye conjugates 38 , but these are generally reserved to excised tissue samples requiring invasive procedures. Alternatively, nanoprobes are being developed with β-cell specificity and high contrast 39 , which may enable clinicians and researchers to non-invasively quantify in vivo endogenous β-cell mass 40 , survival of exogenous transplanted islets 41 and the performance of islet cells in cell replacement therapy 4246 . Various non-invasive imaging techniques are being investigated for the visualization of β-cell mass, including computed tomography (CT), positron emission tomography (PET) and magnetic resonance imaging (MRI) 47 .…”
Section: Diagnosis and Disease Monitoringmentioning
confidence: 99%
“…A recent report using this approach further demonstrated its application to study immune responses after pancreatic islet transplantation 31 . Importantly, this study showed that transplantation into the anterior chamber of the eye provides a natural body window to perform: (1) longitudinal, non-invasive imaging of transplanted tissues in vivo; (2) in vivo cytolabeling to assess cellular phenotype and viability in situ; (3) real-time tracking of infiltrating immune cells in the target tissue; and (4) local intervention by topical application or intraocular injection.…”
Section: Introductionmentioning
confidence: 99%
“…This highlights the challenge in translating findings obtained by conventional in vitro methods into the living animal. In the last decade, visualization of tissues in living animals was considerably improved by technological advances in imaging modalities 2,3,4,5,6 . This has spurred a need for in vivo imaging approaches with feasible application in experimental animal models to enable longitudinal visualization of target tissues non-invasively.…”
Section: Introductionmentioning
confidence: 99%
“…Noninvasive in vivo imaging of pancreatic islets has long remained a formidable challenge for diabetes research (Malaisse and Maedler, 2012;Virostko et al, 2006). Several of the high-resolution approaches that are currently available to image islets in vivo are highly invasive (Leibiger et al, 2012). Methods such as positron emission tomography (PET) and magnetic resonance imaging (MRI) offer great potential for imaging human pancreatic islets in situ, but they are limited by low resolution and sensitivity (Andralojc et al, 2012;Virostko et al, 2006).…”
Section: Introductionmentioning
confidence: 99%